Question number 4 solve.

[tex]\mathsf{Given : \dfrac{3m^2 - 3n^2}{6m - 6n}}[/tex]
[tex]\mathsf{\implies \dfrac{3(m^2 - n^2)}{6(m - n)}}[/tex]
[tex]\bigstar[/tex] We know that : (A² - B²) = (A + B)(A - B)
[tex]:\implies[/tex] (m² - n²) can be written as (m + n)(m - n)
[tex]\mathsf{\implies \dfrac{3(m + n)(m - n)}{6(m - n)}}[/tex]
[tex]\mathsf{\implies \dfrac{(m + n)}{2}}[/tex]
Answer:
Step-by-step explanation:
x² - y² =(x +y)(x -y)
[tex]\frac{3m^{2}-3n^{2}}{6m-6n}=\frac{3*(m^{2}-n^{2})}{6*(m-n)}\\\\=\frac{m^{2}-n^{2}}{2*(m-n)}\\\\=\frac{(m+n)*(m-n)}{2*(m-n)}\\\\=\frac{m+n}{2}[/tex]